Imperative Speech in The Collection of Stories of Kritikus Adinan By Budi Darma: A Pragmatic Study - Wisnu Ismaya; Sintowati Rini Utami (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research aimed to obtain the information about the imperative speech in a collection of stories of Kritikus Adinan by Budi Darma. This study was conducted in April to July 2019. The focus of this research was the speech that seen from the construction of speech and the imperative pragmatic meaning in the collection of stories entitled Kritikus Adinan that written by Budi Darma. The method used in this study is a qualitative descriptive method. The instruments used are data analysis tables consisting of context, speech, construction speech, pragmatic meaning imperatives, and analysis. The results obtained from 238 analysis of speech data, there are 81.93% (195) speech that has imperative pragmatic meanings which consist of (1) imperative pragmatic meanings of command, (2) imperative pragmatic meanings of the orders, (3) imperative pragmatic meanings of the request, (4) imperative pragmatic meanings of petition, (6) imperative pragmatic meanings of the urge, (5) imperative pragmatic meanings of persuation, (7) imperative pragmatic meanings of exhortation, (8) imperative pragmatic meanings of the cross, (9) imperative pragmatic meanings of invitation, (10) imperative pragmatic meanings of request for permission, (11) imperative pragmatic meanings of permit, (12) imperative pragmatic meanings of prohibition, (13) imperative pragmatic meanings of hope, (14) imperative pragmatic meanings of the swearing, (15) imperative pragmatic meanings the provision of congratulations, (16) imperative pragmatic meanings of the suggestion, (17) imperative pragmatic meanings of ngelulu. The frequency of occurrence of speech with the pragmatic significance of the greatest imperative is the speech which has the pragmatic meaning of the command and the orders are 13.3% (26). The frequency of occurrence of speech with the pragmatic meaning of the smallest imperatives is the speech which has the pragmatic meaning imperatives of the greeting of the congratulation is 0.5% (1). The results of this study can be implied in teaching Bahasa Indonesia for students through the use of the imperatives in KD 3.19 which demands the students to analyze the content and the linguistic of drama script that read or watched and KD 4.19 that demands the students to demonstrate a drama script by observing its contents and its specifications in the XI grade of senior high school. Keywords: pragmatic, imperative speech, collection of stories Abstrak Penelitian ini bertujuan untuk memperoleh informasi tentang ujaran imperatif dalam kumpulan cerita Kritikus Adinan karangan Budi Darma. Penelitian ini dilakukan pada bulan April hingga bulan Juli 2019. Fokus penelitian ini adalah ujaran yang dilihat dari konstruksi ujaran dan makna pragmatik imperatifnya pada kumpulan cerita Kritikus Adinan karangan Budi Darma. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Instrumen yang digunakan berupa tabel analisis data yang terdiri atas konteks, ujaran, konstruksi ujaran, makna pragmatik imperatif, dan analisis. Hasil yang diperoleh dari 238 data ujaran hasil analisis, terdapat 81,93% (195) ujaran yang memiliki makna pragmatik imperatif. Dari 195 ujaran, 61% (119) ujaran diwujudkan dalam konstruksi imperatif, 25,1% (49) ujaran diwujudkan dalam konstruksi deklaratif, dan 13,84% (27) ujaran diwujudkan dalam konstruksi interogatif. Dari 195 ujaran yang memiliki makna pragmatik imperatif, terdapat ujaran yang memiliki makna pragmatik imperatif yang terdiri atas (1) makna pragmatik imperatif perintah, (2) makna pragmatik imperatif suruhan, (3) makna pragmatik imperatif permintaan, (4) makna pragmatik imperatif permohonan, (5) makna pragmatik imperatif desakan, (6) makna pragmatik imperatif bujukan, (7) makna pragmatik imperatif imbauan, (8) makna pragmatik imperatif persilaan, (9) makna pragmatik imperatif ajakan, (10) makna pragmatik imperatif permintaan izin, (11) makna pragmatik imperatif mengizinkan, (12) pragmatik imperatif larangan, (13) makna pragmatik imperatif harapan, (14) makna pragmatik imperatif umpatan, (15) makna pragmatik imperatif pemberian ucapan selamat, (16) makna pragmatik imperatif anjuran, dan (17) pragmatik imperatif ngelulu. Frekuensi kemunculan ujaran dengan makna pragmatik imperatif terbesar ialah ujaran yang memiliki makna pragmatik imperatif perintah dan suruhan yaitu 13,3% (26). Frekuensi kemunculan ujaran dengan makna pragmatik imperatif terkecil ialah ujaran yang memiliki makna pragmatik imperatif pemberian ucapan selamat yaitu 0,5% (1). Hasil penelitian ini dapat diimplikasikan dalam pembelajaran Bahasa Indonesia bagi siswa melalui penggunaan ujaran imperatif dalam KD 3.19 yang meminta siswa untuk menganalisis isi dan kebahasaan drama yang dibaca atau ditonton dan KD 4.19 yang meminta siswa untuk mendemonstrasikan sebuah naskah drama dengan memerhatikan isi dan kebahasaannya di kelas XI SMA/MA. Kata Kunci: pragmatik, ujaran imperatif, kumpulan cerita